Disseminated cryptococcosis in a patient taking tocilizumab for Castleman's disease. Issue 2 (February 2018) - Nishioka, Hiroaki; Takegawa, Hiroshi; Kamei, Hiroki
Abstract: Infections occur more frequently in patients receiving biologics. However, cryptococcal infection is uncommon in patients receiving tocilizumab, an interleukin-6 inhibitor, in contrast to patients receiving tumor necrosis factor-α inhibitors. In this report, we describe a case of disseminated cryptococcosis in a 55-year-old man who was receiving tocilizumab every 2 weeks along with daily prednisolone and cyclosporine for Castleman's disease. He initially developed cellulitis on both upper limbs, and his condition worsened despite antibacterial therapy. Chest X-ray scanning and computed tomography demonstrated bilateral pulmonary infiltration. Cryptococcus neoformans was detected in blood, skin, and sputum cultures. He was diagnosed with disseminated cryptococcosis, and successfully treated with liposomal amphotericin B for a week followed by oral fluconazole for 11 months. The findings of this study indicate that cryptococcosis should be considered during the differential diagnosis of infection in patients receiving tocilizumab, especially in the presence of other risk factors for infections or a short tocilizumab dosing interval.